Determinants of green trust on repurchase intentions: a survey of Quick Service Restaurants in Indonesia - Mukhammad Kholid Mawardi; Mohammad Iqbal; Endang Siti Astuti; Rizal Alfisyahr; Andi Mappatompo (Cogent Business & Management, 2024)
This study aimed to determine the interaction between internal and external factors of consumers indicated by perceived values, green products, and environmental behavior on customers' decisions to purchase fast food restaurants' eco-friendly products indicated by green trust and repurchase intention variables. This research involved 336 respondents and employed a survey as an inquiry method. The findings show that consumers' internal factors, namely perceived values, and external factors, namely green products, could significantly affect green trust and repurchase intention that represented the decision of purchasing environmentally friendly products. Meanwhile, the environmental behavior could not influence the consumers to purchase eco-friendly products from fast food restaurants. Finally, this research contributes to a consumer investigation to determine the effects of consumers' internal and external factors to buy eco-friendly products.
Keywords: 650; value; environmental behavior; green marketing; consumer behavior; repurchase intention